DIVERSITY AND CORRELATION OF BODY WIDTH DIMENSIONS OF BALI CATTLE AT PUSAT PEMBIBITAN SAPI BALI UNGGUL, GEROKGAK, BULELENG, BALI - Islamiati, Feren Salsabila; Susari, Ni Nyoman Werdi; Sampurna, I Putu (Buletin Veteriner Udayana, 2022)
Bali cattle are native Indonesian cattle as a result of the long-running domestication of wild banteng and are one of the germplasm that has the potential to be developed. This study aims to determine the diversity and correlation of body width dimensions of bali cattle. The samples used were 25 cows that were mature and had given birth. The data obtained were analyzed by descriptive analysis and biplot analysis and then presented in the form of tables and graphs. The results showed that the greatest coefficient of variation (various) was the width of the buttocks, which was 29.25%, followed by the neck width, which was 24.28%. chest width is 17.01%, cheek width is 13, 28%, steering width is 13.00% and the most uniform is head width 8.13%. While the correlation between the dimensions of the width obtained results that head width is positively correlated with cheek width and rudder width and is not correlated with chest width and neck width, but is negatively correlated with buttock width.